ANALISIS PUSAT PERTUMBUHAN EKONOMI KAB. SINGKIL - Okta Kurniawan TB; Sirojuzilam Sirojuzilam (Ekonomi dan Keuangan, 2014)
This research intended for any identifying characteristic owned regency of aceh singkil as center area growth, namely region fast-growing and fast forward who owns the superior sector, and has economic linkages with other. For this purpose use the analysis tools Location Quotient ( LQ ), Klassen Tipology dan Gravity Model.LQ result analysis showing that almost all economic sectors in regency of aceh singkil is superior sectors but sector that contributes largest was agriculture and the trade, hotel, and restaurant . Through tipologi klassen obtained the result that district aceh singkil including in the classification of income per capita growth, high and high compared with province of aceh or the fast-growing and fast forward. Gravity model described that all districts of regency of aceh singkil is districts gunung meriah, that has seen from its gravitational attraction of the population and its economic activity.From all the calculations that have been done, can be drawn the conclusion that the regency of aceh singkil is fast growing and fast forward, backed by its superior sectors which have competitiveness against other areas, as well as supported also by the gunung meriah district which is the gravitational pull of the powerful social and economic side.Key words : Growth Center, Location Quotient ( LQ ), Klassen Tipology , and Gravitation Model